Stimulation of the internal superior laryngeal nerve as a potential therapy for obstructive sleep apnea in a porcine model - Maurer, Joachim T.; Huseynov, Jamal; Hochreiter, Jakob; Perkins, Justin D. (Journal of applied physiology, 2024)
Download figureDownload PowerPoint